Simulation-Based Analysis for Optimizing ID Card Holder Injection Molding Using Autodesk Fusion - Adinda Rahmah Shalihah; Edwin Sahrial Solih; Sanurya Putri Purbaningrum; Ridho Hans Gurning; Fredy Sumasto; Desy Agung (Infotekmesin, 2026)
This study aims to determine the most suitable initial injection-molding condition for a polypropylene (PP) ID card holder using Autodesk Fusion. Five paired melt-temperature and mold-surface-temperature conditions were evaluated at injection times of 0.5 and 1.0 s, resulting in ten simulation cases. The contribution of this study is a multi-response screening approach before mold fabrication that simultaneously considers fill confidence, injection pressure, quality prediction, cooling time, air traps, weld lines, sink marks, and warpage. All conditions achieved fill-confidence values of 99.67–100%. P4 at 1.0 s produced the highest quality prediction of 85.81% but required 11.87 s of cooling. P2 at 1.0 s was selected as the most balanced condition, with 85.27% quality prediction, 44.98 MPa injection pressure, 4.95 s cooling time, approximately four air-trap areas, 18 weld-line faces, a 0.027 mm sink mark, and 1.736 mm warpage. These simulation results require experimental validation.